Sistem Pemrosesan Surat Menyurat pada Kantor POS Peureulak Kabupaten Aceh Timur - Maulida; M Djamil (Jurnal Ekonomi Manajemen dan Sekretari, 2021)
The Correspondence Processing System at the Peureulak Post Office, East Aceh Regency is a system used to manage the sending and receiving of letters at the post office. This system was created to increase efficiency and effectiveness in managing correspondence, to provide better service to the community. In developing this system, the methods of observation, interviews, and literature studies were used to understand the needs and existing business processes at the Peureulak Post Office. Then, an analysis of the data obtained is carried out to design a system that suits these needs. The Correspondence Processing System at the Peureulak Post Office in East Aceh Regency consists of several modules, including the letter receiving module, the mail sending module, the mail tracking module, and the reporting module. This system uses computer and network technology to connect all modules so they can work in an integrated manner. With the Correspondence Processing System at the Peureulak Post Office, East Aceh District, it is hoped that sending and receiving letters can be done more quickly and efficiently. In addition, this system can also make it easier for users to track mail and produce reports that are more accurate and detailed.